The unique biochemistry of methanogenesis - Deppenmeier, Uwe (Progress in Nucleic Acid Research and Molecular Biology, 2002)
Methanogenic archaea have an unusual type of metabolism because they use H2 + CO2, formate, methylated C1 compounds, or acetate as energy and carbon sources for growth. The methanogens produce methane as the major end product of their metabolism in a unique energy-generating process. The organisms received much attention because they catalyze the terminal step in the anaerobic breakdown of organic matter under sulfate-limiting conditions and are essential for both the recycling of carbon compounds and the maintenance of the global carbon flux on Earth. Furthermore, methane is an important greenhouse gas that directly contributes to climate changes and global warming. Hence, the understanding of the biochemical processes leading to methane formation are of major interest. This review focuses on the metabolic pathways of methanogenesis that are rather unique and involve a number of unusual enzymes and coenzymes. It will be shown how the previously mentioned substrates are converted to CH4 via the CO2-reducing, methylotrophic, or aceticlastic pathway. All catabolic processes finally lead to the formation of a mixed disulfide from coenzyme M and coenzyme B that functions as an electron acceptor of certain anaerobic respiratory chains. Molecular hydrogen, reduced coenzyme F420, or reduced ferredoxin are used as electron donors. The redox reactions as catalyzed by the membrane-bound electron transport chains are coupled to proton translocation across the cytoplasmic membrane. The resulting electrochemical proton gradient is the driving force for ATP synthesis as catalyzed by an A1A0-type ATP synthase. Other energy-transducing enzymes involved in methanogenesis are the membrane-integral methyltransferase and the formylmethanofuran dehydrogenase complex. The former enzyme is a unique, reversible sodium ion pump that couples methyl-group transfer with the transport of Na+ across the membrane. The formylmethanofuran dehydrogenase is a reversible ion pump that catalyzes formylation and deformylation of methanofuran. Furthermore, the review addresses questions related to the biochemical and genetic characteristics of the energy-transducing enzymes and to the mechanisms of ion translocation.